PENGARUH APLIKASI BIOCHAR TONGKOL JAGUNG DIPERKAYA ASAM NITRAT TERHADAP KADAR C-ORGANIK, NITROGEN, DAN PERTUMBUHAN TANAMAN JAGUNG PADA BERBAGAI TINGKAT KEMASAMAN TANAH - Hadi Yuananto; Wani Hadi Utomo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The need for food in Indonesia is relatively large, but not followed by optimal land conditions. One of the efforts to improve the quality of land that can be applied is biochar. Biochar used comes from corn cobs with nitrate acid enrichment. The purpose of this research is to know the effect of biochar application of corn cobs enriched nitric acid to C-Organic content, Nitrogen, and vegetative growth of corn plants at different soil pH. The research was implemented in September 2016 - March 2017 at the Tribhuwana Tunggadewi Experimental Garden. This study used a factorial randomized block design with two factors and three replications. The first factor of soil pHs were soil from West Borneo (As), Wajak (Ne), and NTT (Ba). The second factor of biochar applications were without biochar (K), biochar (Bio), and biochar enriched nitrate acid (BioN). The average effect of pH with biochar was no interaction except on the N-total content. However, overall application of 5 t ha-1 of biochar and biochar enriched nitrate acid had better C-organic, N-total, and growth of maize than control treatment on each soil.